Ask the Experts: Chronic neck pain: risk factors, consequences and solutions. (July 2013) - Andersen, Lars L
Lars L Andersen, MSc PhD, is Professor of Musculoskeletal Disorders at National Research Centre for the Working Environment in Copenhagen (Denmark). With a background in exercise physiology, he has a special interest in the effect of strength training on health, performance and disease. Currently, he performs epidemiological and interventional research primarily in the field of musculoskeletal disorders, but also in psychosocial work environment, behavioral psychology, stroke, early aging, physical activity and workplace health promotion. He has led several research projects and published more than 90 original articles with peer-review in international journals. He is an editorial board member of BMC Musculoskeletal Disorders, Journal of Aging and Health and ISRN Pain . His research on treatment of musculoskeletal disorders using strength training and kettlebell training has been highlighted in the media, for example, by USA Today, the New York Times and Reuters .